Implementation of Movie Making as Instagram Content in the Extended Speaking Class - Christanty Yudha Bestari, Ade; Dinar Faiza; Meilina Haris Mayekti; Rosyid Dodiyanto (Educalitra: English Education, Linguistics, and Literature Journal, 2024)
This journal contained analysis of implementation in movie making as Instagram Content in the Extended Speaking Class. Instagram as a popular media for improving speaking skills in the era of gadgets. Most of people have Instagram account in the recent time. They are very active in using Instagram. Anything can be viral on this platform. This study presented the students’ perceptions of implementation in movie making as Instagram content in the Extended Speaking Class. The data were analyzed by using qualitative standard of research using interview. The outputs achieved in this study are accredited national journals, book chapters, seminars, and online news media publications. The result of this research that there were the influences from implementation in movie making as Instagram content in the extended speaking class. The first showed that participants got enhancing vocabularies from the movie dialogue. Secondly, the participants likely practiced English Pronunciation. Then, the implementation of movie making became a media of expression for increased confidence in speaking. The last result is creativity building.